KEDUDUKAN ANAK ADOPSI MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA - Riza Yudha Patria (Fakultas Hukum Universitas Tulang Bawang, 2021)
Absract Children are interpreted as a gift from God to make them happy and strengthen the bond of love between a husband and wife. In fact, there are married couples who do not have the desired offspring, for various reasons, ranging from medical causes to hereditary factors. Married couples will try to bring children in the middle of their domestic life, by adopting children. The problem in this paper is the requirements for adopting a child and the status of an adopted child according to civil law. The purpose of this study was to find out how the process of applying for child adoption. The approach method used in this research is the statutory approach. The method of presenting data in this research is done descriptively. The analysis used in this paper is conceptual. The results of the study indicate that the conditions for adopting a child can be carried out in accordance with the Circular Letter of the Supreme Court of the Republic of Indonesia NO. 6/83 which regulates how to adopt a child stating that to adopt a child, you must first submit an application. Keywords: Civil law, Adoption, Child